Pengaruh Profitabilitas, Struktur Modal, Ukuran Perusahaan, dan Kebijakan Dividen terhadap Nilai Perusahaan Farmasi yang Terdaftar di BEI Tahun 2018-2022 - Dionisius Kristianto Nugraha (AKUNTANSI 45, 2024)
The analysis carried out aims to identify the influence of profitability, capital structure, company size, dividend policy on company value. This analysis was carried out on pharmaceutical institutions listed on the IDX for the period 2018 - 2022. This observation sample was selected through a purposive sampling method. This method uses financial reports and annual details that can be seen on the official page of the Indonesia Stock Exchange. Observations using a multiple regression approach. In this analysis, 45 data were found. The analysis found shows that profitability, and dividend policy have a comprehensive impact on company value, with a coefficient of determination (adjusted R2) of 0.248. However, no significant influence was found on the variables of profitability, company size, and dividend policy on company value.